Low compression ratio diesel engines fueled with biodiesel by using spark-induced compression ignition. (June 2015) - Yamane, Koji; Kondo, Chihiro; Kondo, Daichi; Kawasaki, Kiyoshi
The objective of this study was to demonstrate a novel combustion system in which autoignition is induced by spark discharge into a pre-mixture formed during a long ignition delay time in a direct injection diesel engine with a low compression ratio. The effects of spark discharge on the autoignition process were investigated by changing the spark timing, injection timing, equivalence ratio and fuel amount. The fuel used was lauric acid methyl ester, a fatty acid methyl ester that is relatively volatile and exhibits higher ignition quality than standard diesel fuel. The results obtained with a single-cylinder common-rail direct injection diesel engine show that spark-induced compression ignition combustion was obtained with a volumetric efficiency of 34%. In this study, the autoignition timing was advanced by spark discharge and was controlled by the spark timing within 5° crank angle. We also observed the spark-induced compression ignition combustion flame in a constant volume combustion vessel using direct high-speed photography and OH radical chemiluminescence spectroscopy by means of a combination of an optical band-pass filter, an image intensifier and a charge-coupled device camera. The results showed that spark-induced compression ignition occurs not by flame propagation due to spark ignition but by autoignition of a spray pre-mixture. It was also evident that autoignition is induced by transportation of OH radicals formed at the spark plug by the spray flow.